Experimental Investigation on the Fatigue Behavior on Honeycomb Sandwich Composite Panels - Ahmed Ali Khalid; Fadhel Abbas Abdulla; Mushtaq Al-Sharify (Tikrit Journal of Engineering Sciences, 2023)
This paper aims to study the dynamic behaviors of particular sandwich panels manufactured using three specifications of aluminum honeycomb core with fiberglass or aluminum face-sheet materials. Three groups of panels were designed and manufactured, each including three different sorts of samples, all fabricated with the same thickness. A cantilever fatigue test was conducted on specimens, and the results were collected and presented in curves to detect the factors that affect the panel's endurance. The finding showed that the specimens with aluminum skin had more probability of face-sheet/core delamination. Samples of fiberglass covers showed face-sheets cracks or cores cracks more than delamination failure, while samples of epoxy-filled cores experienced the specimen’s global crack. Generally, specimens with aluminum covers and epoxy-filled cores resisted fatigue load more than other specimens. The larger honeycomb cell-size specimens showed more probability to face-sheet/core delamination failures than samples with smaller cell-size cores.